IL‐25 prevents and cures fulminant hepatitis in mice through a myeloid‐derived suppressor cell‐dependent mechanism. Issue 4 (26th August 2013) - Sarra, Massimiliano; Cupi, Maria Laura; Bernardini, Roberta; Ronchetti, Giulia; Monteleone, Ivan; Ranalli, Marco; Franzè, Eleonora; Rizzo, Angelamaria; Colantoni, Alfredo; Caprioli, Flavio; Maggioni, Marco; Gambacurta, Alessandra; et al.
<x xml:space="preserve">Abstract</x> Fulminant hepatitis (FH) is a disease characterized by massive destruction of hepatocytes with severe impairment of liver function. The pathogenesis of FH is not fully understood, but hyperactivity of T cells and macrophages with excessive production of cytokines are important hallmarks of the condition. In this study, we investigated the role of interleukin (IL)−25 in FH. IL‐25 expression was evaluated in patients with FH and in livers of mice with FH induced by D‐galactosamine (D‐Gal) and lipopolysaccharide (LPS). Mice were treated with IL‐25 before D‐Gal/LPS‐induced FH and before or after concanavalin A (ConA)‐induced FH. Mononuclear cells were isolated from livers of mice treated with or without IL‐25 and analyzed for GR1+CD11b+ cells. CFSE‐labeled T cells were cocultured with GR1+CD11b+ cells and their proliferation was evaluated by flow cytometry. Mice were also treated with a depleting anti‐GR1 antibody before IL‐25 and D‐Gal/LPS administration. IL‐25 was constitutively expressed in mouse and human liver and down‐regulated during FH. IL‐25 prevented D‐Gal/LPS‐induced FH and this effect was associated with increased infiltration of the liver with cells coexpressing GR1 and CD11b. In vitro studies showed that GR1+CD11b+ cells isolated from mice given IL‐25 inhibited T‐cell proliferation. Consistently, in vivo depletion of GR1+ cells abrogated the protective effect of IL‐25 in experimental D‐Gal/LPS‐induced FH. IL‐25 was both preventive and therapeutic in ConA‐induced FH. Conclusions: IL‐25 expression is markedly reduced during human and experimental FH. IL‐25 promotes liver accumulation of GR1+CD11b+cells with immunoregulatory properties. (Hepatology 2013;58:1436–1450)